1997
DOI: 10.1097/00002060-199705000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effective Physical Therapy for Chronic Obstructive Pulmonary Disease

Abstract: Respiratory function and arterial blood gas were examined before and after a two-month exercise program performed in a pool filled with hot spring water in 22 patients (70.9 +/- 9.1 years of age) with stable chronic obstructive pulmonary disease (12 cases of bronchial asthma and 10 cases of pulmonary emphysema) treated at our hospital between 1991 and 1994. The ratio of forced expired volume in one second to forced vital capacity (FEV1%) was significantly increased after the exercise program (P < 0.05), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
2
21
0
5
Order By: Relevance
“…[21][22][23] A small body of research has examined the physiological effects of exercise in water for people with respiratory diseases. 6,10 Reported benefits need to be assessed in greater depth, but they are supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[21][22][23] A small body of research has examined the physiological effects of exercise in water for people with respiratory diseases. 6,10 Reported benefits need to be assessed in greater depth, but they are supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 55%
“…6 In a number of studies of hydro-therapy in a hospital setting, Kurabayashi and colleagues concluded that exercise in a hot spring-water pool may be useful in COPD. [7][8][9][10] Exercise in water has characteristics that may make it beneficial in the elderly. 11,12 These observations suggest that people with COPD may find exercise in water more suitable.…”
Section: Introductionmentioning
confidence: 99%
“…However, few of them used aquatic respiratory exercise with such ends. A lone study 15 used the aquatic modality exclusively, but its results could not be directly compared with those of our study, since the sample type, variables evaluated, and conditions of treatment were different. The authors found a significant increase in the FEV 1 (forced expiratory volume in 1 second) for subjects with chronic obstructive pulmonary disease (COPD) who performed respiratory exercises in warm water (38ºC).…”
Section: Discussionmentioning
confidence: 95%
“…29 Kurabayashi et al got similar results to this study, when they did not find improvement in expiratory parameters in subjects with COPD who underwent aquatic RMT. 15 Kurabayashi et al reported improvement in FEV 1 and peak flow of subjects with emphysema who accomplished expiration under water. 31 They believed that the added resistance given by water resistance was similar to the pursed-lips expiration, preventing the small airway from collapsing.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los estudios revisados hay varios que utilizan la natación como forma de entrenamiento, pero ninguno nombra un entrenamiento físico en piscina climatizada como medio de prevención de AIE. El único que se aproxima es un estudio realizado en Japón (Kurabayashi, 1997) en pacientes con enfermedad pulmonar obstructiva crónica (EPOC), donde utilizaban una piscina a 38º C con agua de manantial para realizar un programa de ejercicios, obteniendo mejoría en parámetros espirométricos pero no mencionan si se desminuían las crisis de broncoespasmo.…”
Section: Discussionunclassified